Dwór rodziny Rostworowskich w Kęble miejscem edukacji i wychowania dzieci i młodzieży - Filiks-Bielecka, Karolina (Biuletyn Historii Wychowania, 2018)
This article presents the family manor of the Rostworowski family in Kębło and its importance to the education and upbringing of children and adolescents. After 1949, social and educational activities took place in Kębło manor. In the article, I present various forms of caring for children and adolescents, organized in the manor house. It hosted an orphanage, a State-owned Educational Institute for Handicapped Children, which today is a Boarding Special Education School and a Vocational Preparation School. The State-owned Orphanage operated in Kębło between 1947 and 1982. Now it houses a Special Education Centre and a three-year Work Vocational Preparation School where pupils absorb the knowledge and acquire the skills to help them lead independent lives. As part of practical classes, students grow and care for vegetables and herbs, tend rock gardens and plants, bake cakes, make preserves and prepare simple dishes.